Stretching the Limits of Renal Transplantation in Elderly Recipients of Grafts from Elderly Deceased Donors - Peters-Sengers, Hessel (J Am Soc Nephrol, 2017)
An increasing number of elderly patients (≥65 years) receive a donor kidney from elderly donors after brain death (DBD) or after circulatory death (DCD). These organs are allocated within the Eurotransplant Senior Program, but outcomes must be evaluated. From the Dutch Organ Transplantation Registry, we selected 3597 recipients (≥18 years) who received a first DBD or DCD kidney during 2002–2012, and categorized them as young or elderly recipients receiving a graft from either a young or elderly donor, stratified by donor type. In multiple logistic regression analysis, elderly recipients of elderly DCD kidneys experienced more delayed graft function and acute rejection than did elderly recipients of young DBD kidneys (odds ratios 10.43 [95% confidence interval (95% CI), 5.75 to 18.91] and 2.78 [95% CI, 1.35 to 5.73], respectively). In Cox regression analysis, elderly recipients of elderly DCD kidneys had a 5-year mortality risk higher than that of elderly recipients of young DBD kidneys (hazard ratio, 1.86; 95% CI, 1.15 to 3.02). Elderly recipients of elderly kidneys had a 5-year mortality rate comparable to that of waitlisted elderly patients remaining on dialysis. Among elderly recipients, 63.8% of those who received elderly DCD kidneys, 45.5% of those who received elderly DBD kidneys, and approximately 26% of those who received young DBD or DCD kidneys had an eGFR<30 ml/min per 1.73 m(2) (including primary nonfunction) after 1 year. In conclusion, improving donor selection and preservation is warranted if the allocation of elderly DCD grafts to elderly recipients is to be expanded.